Penggunaan Media Gambar untuk Meningkatkan Diksi Keterampilan Menulis Paragraf Deskripsi Siswa Kelas VII-B SMPN 2 Dawarblandong - Dina Sri Puspitasari; Dinda Wulansari; Khusnul Nur Mawar Sari; Mita Miftaqul Muhclisah (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to describe the improvement of descriptive paragraph writing skills among students at SMPN 2 Dawarblandong using image-based media. A qualitative method was employed, utilizing observation as the data collection technique. The results indicate an improvement in descriptive writing abilities following the implementation of this media. Prior to using image-based media, students struggled to expand their ideas, select precise vocabulary, and describe objects in detail. After using the media, however, students were able to produce writing featuring more accurate and varied word choices, as well as clearer and more appropriate object descriptions. Thus, the use of image-based media has proven to be an effective tool.